The effect of political dynasties on human development in Philippine provinces a 2012 study with evidences from electoral term 2010-2013 - Publico, Anna Sophia G. (School of Economics, University of the Philippines Diliman, 2018)
This paper aims to juxtapose the prevalence of political dynasties to the human development of every province in the Philippines, and see whether the two are correlated. By deriving data on the percentage of all elected politicians for the year 2010 who have dynastic backgrounds and relating this to their corresponding province_s Human Development Index (HDI) scores for the year 2012, the paper aims to see how one acts as a function of another. The paper finds that to some extent, the presence of political dynasties negatively affects the human development of their constituency. Though these variables share an inverse relationship, the paper recognizes that the level of human development is more so determined by a mix of both political and non_political factors. The study finds that the HDI scores per province are more significantly affected by factors other than a higher share of dynastic politicians in power.